Unsteady LPT Blade Effects on Outlet Guide Vane Heat Transfer. Analysis of transient thermal loads induced by blade wakes in turbine rear structures - Dahlin, Wilhelm (My University, 2025)
Accurate thermal modeling in turbine rear structures (TRS) of aero-engines is crucial due to the high temperature air flow and cyclic thermal stresses induced by unsteady blade wakes from upstream low-pressure turbine (LPT) blades. Current industry practices predominantly rely on steady-state computational fluid dynamics (CFD) simulations to predict heat transfer coefficients (HTC). However, these models commonly underpredict HTC when compared to experimental measurements, primarily due to their inability to capture transient and unsteady effects. In collaboration with GKN Aerospace Sweden, this thesis has focused on developing and analysing a two-dimensional transient CFD model of Outlet Guide Vane (OGV) heat transfer using sliding mesh techniques and advanced turbulence models, notably the SSTtransition turbulence model. Validation of this model was conducted against experimental HTC data obtained from a 1.5-stage test rig at Chalmers. The transient simulations reveal clear periodic fluctuations in HTC due to the rotor blade wakes, phenomena inherently missed by steady-state models. However, despite capturing temporal HTC variations and unsteady flow behaviour the transient CFD approach still resulted in HTC underpredictions compared to experimental data as well as 2D and 3D steady-state CFD models. This discrepancy is attributed not only to limitations inherent in two-dimensional modeling but also to the need for more advanced turbulence modeling and potential inaccuracies stemming from an outdated mesh study based on incorrect boundary conditions. The study suggests further research should focus on resolving these issues through refined turbulence modeling strategies, accurate boundary condition implementation, and rigorous mesh studies to enhance predictive accuracy as well as industrial relevance and applicability.
Keywords: heat transfer; convection; heat transfer coefficient (HTC); computational fluid dynamics (CFD); transient; turbine rear structure (TRS); outlet guide vane (OGV); turbulence; transition